Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.4028/www.scientific.net/amr.694-697.3141
|View full text |Cite
|
Sign up to set email alerts
|

Using Axiomatic Design and TRIZ in (re)Designing of Product Architecture Toward Upgradable Products

Abstract: The movements to personalized products and up-to-date technology speed up the time of products become obsolete (partially obsolete) before the end of their life. Thus, the capability to design product more flexible is the key competitive factor leads to secure product cost and extend the product life time. In this paper, the (re)design methodology that leans on Axiomatic design and TRIZ has been developed and implemented to enhance flexibility of a product meeting customer’s requirements and support future cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The effectiveness of many applications was analyzed, revealing our work's reasonable application in practice. The reverse zigzagging approach adapted from [1] was used in the analysis of the existing design stage to break down the current design of a mechatronic product and to reflect the technique of a descending order for the product structure and design hierarchy to the lowest level by applying AD (in the case of an AGV). The findings revealed three layers of multidisciplinary relationships between DPs and FRs at their fundamental level (mechanical, electrical, and information technology).…”
Section: Analyzing the Results And Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effectiveness of many applications was analyzed, revealing our work's reasonable application in practice. The reverse zigzagging approach adapted from [1] was used in the analysis of the existing design stage to break down the current design of a mechatronic product and to reflect the technique of a descending order for the product structure and design hierarchy to the lowest level by applying AD (in the case of an AGV). The findings revealed three layers of multidisciplinary relationships between DPs and FRs at their fundamental level (mechanical, electrical, and information technology).…”
Section: Analyzing the Results And Discussionmentioning
confidence: 99%
“…Compared with two previous studies [1,22], in terms of modeling efficiency, the modeling approach suggested in this study to analyze the information data in an original design provides a number of advantages. Due to the interconnections of the analyzed components, it is comparatively less difficult.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations